Implementasi mediasi dalam sistem peradilan agama - Sururie, Ramdani Wahyu (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
This study aimed at describing the background of the birth of the policy on mediation in the Religious of Court and to understand and identify the procedures, barriers and efforts to improve religious court settlement through mediation. The method used is descriptive research method analysis of mediation theory and implementation in the religious court. The study found a number of findings that can give significance to the development of science in the field of procedural law of religious courts, which ishlah theory that can be used as a grand theory to study dispute resolution and mediation triangle theory that can be used as an operational theory (applied theory) in seeing the success of mediation in the judiciary. As for the successful implementation of the policy of mediation can be done with a number of strategies.